1999
DOI: 10.1111/j.1708-8208.1999.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Astra Tech and Brånemark System Implants: A Prospective 5‐Year Comparative Study. Results after One Year

Abstract: Abutment connection with Astra Tech implants was simpler than the corresponding surgery with Brånemark System implants and the survival rate of Astra Tech implants was higher than that of Brånemark system implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 5 publications
3
85
0
4
Order By: Relevance
“…This loss begins at the neck of the implant and spreads to the first thread of the body of the implant or to the first contact between the bone and the rough surface of the implant (3). Peri-implant bone reabsorption depends on a number of factors such as the surface of the neck (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and reduction of the implant platform (11)(12)(13). There is no agreement regarding the influence of performing surgery in one or two steps (14)(15)(16) or of the cylindrical or conical morphology of the neck (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…This loss begins at the neck of the implant and spreads to the first thread of the body of the implant or to the first contact between the bone and the rough surface of the implant (3). Peri-implant bone reabsorption depends on a number of factors such as the surface of the neck (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and reduction of the implant platform (11)(12)(13). There is no agreement regarding the influence of performing surgery in one or two steps (14)(15)(16) or of the cylindrical or conical morphology of the neck (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported high clinical success rates for titanium grit-blasted implants, up to 10 years after implantation 30,31 . Comparative clinical studies gave higher marginal bone levels and survival rates for TiO2 grit-blasted implants than for machined turned implants 32,33 . Wennerberg et al 13 demonstrated with a rabbit model that grit-blasting with TiO2 or Al2O3 particles gave similar values of bone-implant contact, but drastically increased the biomechanical fixation of the implants when compared to smooth titanium.…”
Section: Roughening Of Implants By Grit-blastingmentioning
confidence: 95%
“…The pullout strength implant, widely studied in the Medical Orthopedics, is multifactorial and is related to bone mineral density, with the implant design and surgical technique, and it is proportional to thread surface in contact with the bone tissue, to avoid its releasing and classifies it as a property of stability of the screw 12 . Nowadays, there are a few available reports in the literature about the tensile strength of dental implants, which it could certainly contribute to the study of primary stability and its relation to the design of implants, where its proper selection is imperative to decrease the magnitude, quantity, and type of loads imposed on the implant / bone interface 13 .…”
Section: Introductionmentioning
confidence: 99%